Studies on the Fate of Coagulation Factors during the Clotting of Normal and Pathological Blood - Hougie, Cecil (Thrombosis and Haemostasis, 1959)
In a mild case of Stuart factor (SF) deficiency and in a patient with hemophilia B (factor IX deficiency) consumption of AHF (factor VIII) was normal but was abnormal in more severe examples of these diseases. This finding reconciles previously conflicting reports. Factor V utilisation was abnormal in moderately severe cases of SF deficiency, hemophilia A and hemophilia B but normal in mild cases of SF deficiency and hemophilia B. A mild case of hemophilia A was not studied. These findings would be expected from the modern concept of blood coagulation. However, the findings with respect to AHF are equally well explained if AHF is destroyed by some intermediate product of blood coagulation, such as thrombin, appearing at the time of the appearance of fibrin.The concentration of SF was found to remain constant during the clotting of both normal blood and blood deficient in factor VILThe concentration of factor VII during the coagulation of normal blood remained constant until the appearance of fibrin. The concentration then increased, but this finding was not consistently obtained. No abnormality in the fate of factor VII during the clotting of blood deficient in SF was found.